EFFECTIVENESS ANALYSIS OF COMPLIANCE WITH ENVIRONMENTAL LEGISLATION IN THE ROSTOV REGION - Zhovtenko, K. A.; Dymnikova, O. V.; Shapovalov, K. A. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2018)
The paper deals with the main ways of sustainable development strategy of Russia at ecological crisis recovery. The study focuses on the administrative and legal aspect of the problem. The article analyzes changes in environmental legislation for the period from 2013 to 2017. Monitoring of ecological violations in the territory of the Rostov region for the specified period has been conducted. The paper provides numerical evaluation andcomparison of damage to the natural environmentfrom violations and penalties in administrative responsibility